Industrialised Building System (IBS) Quality Testing For Disaster Resilience From Technical And Non-Technical Perspectives - Moreen, Daryl Justine (Universiti Sains Malaysia, 2018)
The construction industry plays an important part in the socio-economic development of a developing nation. This industry is a distinct sector of the economy which makes direct contribution to the country’s economic growth and also provides the basis upon which the other sectors can grow. Increased adoption of the Industrialised Building System (IBS) is one of the rapid encouragement efforts made by the Malaysian government to enhance the construction industry. IBS refers to a construction technique whereby building components are manufactured in a controlled environment, either on-site or off-site, and then installed or erected into construction. The main goal of this research is to determine IBS quality testing whether it is disaster resilient in terms of technical and non-technical perspectives. This research to determine the priority factors in IBS quality testing for disaster resilience in building projects from the perspective of stakeholders in the construction industry. This research was performed by conducting a quantitative and qualitative research among 40 respondents. At the end of the research, materials and durability criteria are ranked as the priority criteria under the technical factor category while productivity and economics are the highest ranked criteria under the non-technical category. It is concluded that the technical factors are perceived to be more dominant in terms of IBS quality testing for disaster resilience while non-technical factors also play their roles but are less significant compared to technical factors for IBS quality testing. Based on this research, it is expected that IBS can be further improved in terms of its quality and expand its market at the international level in disaster management.